Allelopathy Test of Cyperus Rotundus Extract on Germination and Early Growth of Spiny Amaranth Weed (Amaranthus spinosus) - Amrullah, Riyan; Indarwati, Indarwati; Susilo, Achmadi (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2024)
Nut grass is defined as a weed that can reduce agricultural yields because it contains allelopathic compounds which have a negative impact on the sprouts and initial growth rate of spinach weed. The written research aims to find out whether allelopathic extracts from sedge grass can influence the germination and initial growth of thorn spinach weed. The research was carried out using a Completely Randomized Design (CRD) consisting of four treatments, each repeated six times. The treatment is defined as: A0 as a control with water, A1 with 50 grams of tekhi per liter of water, A2 with 100 grams of tekhi per liter of water, and A3 with 150 grams of tekhi per liter of water. The results of the study showed that in treatment A3 (150g tekhi/L water) on the last day, the allelopathic extract of tekhi caused abnormalities in 75.17% of spinach spinach seed sprouts. In polybags, A3 treatment (150g tekhi/L water) on the last day reduced the growth rate of the number of seedlings from 25 plants to only 1 plant (96%), with a seedling height of 1 cm and a number of leaves of 3.67 pieces. The higher the treatment dose, the greater the effect in suppressing germination and initial growth of thorn spinach weed.